Use of ecolabels by Finnish circular economy forerunner companies : a current perspective - Saarinen, Iina (2021)
New solutions are required as the current linear economic model is causing environmental, social and economic problems, and the current production and consumption patterns are unsustainable. Transitioning towards sustainability and adopting a new circular economic model can provide solutions for the present issues. Companies have much responsibility in the transition process and can contribute to making consumption and production sustainable. However, companies require tools to make the required changes. In literature, ecolabels have been suggested as tools that can help companies achieve their circular economy and sustainability-related goals and help transform the current consumption and production practices. The current thesis is a quantitative survey study aimed at figuring out how Finnish forerunner companies in circular economy perceive the use of ecolabels and whether or not the companies use ecolabels to achieve their circular economy-related goal. The theoretical framework of the study focused on sustainability, the circular economy, and ecolabels. In addition, the construction of the theoretical framework was also supported by reviewing sustainability transition, the presentation of sustainability and circular economy based business models, and the mapping of the relationship between ecolabels and the circular economy. The data collection was conducted via a survey sent to 214 Finnish companies. Thirty-nine companies responded to the survey. The thesis results reveal that most of the surveyed companies do not currently have ecolabels in use, and only one company reported using ecolabels for achieving their circular economy-related goals. In total, ecolabels were used by nine of the respondents. The most significant drivers for ecolabel use were found to be gaining a competitive advantage, encouraging consumers to buy the company's products, increasing the value of the products, and increasing the company's value. The most significant barriers to using ecolabels were the high costs of ecolabels and the length of the obtaining process. In addition, it was found that companies that are using ecolabels are facing a lack of benefits and an influx of challenges with the use of ecolabels. Therefore, more research is still needed into the usability of ecolabels and how all kinds of companies, especially SMEs, could benefit from ecolabels when transitioning towards a circular economy.